2018
DOI: 10.1073/pnas.1816189115
|View full text |Cite
|
Sign up to set email alerts
|

Role of human Hv1 channels in sperm capacitation and white blood cell respiratory burst established by a designed peptide inhibitor

Abstract: Using a de novo peptide inhibitor, Corza6 (C6), we demonstrate that the human voltage-gated proton channel (hHv1) is the main pathway for H+ efflux that allows capacitation in sperm and permits sustained reactive oxygen species (ROS) production in white blood cells (WBCs). C6 was identified by a phage-display strategy whereby ∼1 million novel peptides were fabricated on an inhibitor cysteine knot (ICK) scaffold and sorting on purified hHv1 protein. Two C6 peptides bind to each dimeric channel, one on the S3–S4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 63 publications
2
66
0
Order By: Relevance
“…Until today, no specific blocker/inhibitor of the channel has been found. However, many interesting inhibitor candidates are under investigation [54][55][56][57][58][59]. The well investigated is the transition metal zinc, which was given its modern name by the sixteenth-century academic Paracelsus.…”
Section: Introductionmentioning
confidence: 99%
“…Until today, no specific blocker/inhibitor of the channel has been found. However, many interesting inhibitor candidates are under investigation [54][55][56][57][58][59]. The well investigated is the transition metal zinc, which was given its modern name by the sixteenth-century academic Paracelsus.…”
Section: Introductionmentioning
confidence: 99%
“…Normal tyrosine phosphorylation was observed in spermatozoa capacitated in the presence of TeNT‐CPP, suggesting TeNT‐CPP does not prevent other capacitation‐associated events. In this regard, we have recently published the action of Corza6 (C6), a peptide with inhibitory activity over hHv1 (human voltage‐gated proton channel) (Zhao et al ., ). This channel extrudes H + during capacitation in human spermatozoa.…”
Section: Discussionmentioning
confidence: 97%
“…This channel extrudes H + during capacitation in human spermatozoa. Capacitation in the presence of C6 inhibits acrosomal exocytosis, but does not block tyrosine phosphorylation (Zhao et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The identification of novel modulators of H V 1 channel would be valuable either as drug candidates or as pharmacological tools to investigate the structure and function of this channel. Recently, Zhao et al identified a novel H V 1 channel toxin, Corza6, from the ICK toxins permutation library using a phage‐display strategy (Zhao et al, ). Both Corza6 and AGAP/W38F inhibit H V 1 currents by trapping the S4 voltage sensor in deactivated states, and these effects could be counteracted by strong depolarization.…”
Section: Discussionmentioning
confidence: 99%